PROGRAM PEMBERIAN MAKANAN TAMBAHAN DALAM UPAYA MENURUNKAN ANGKA STUNTING DI KOTA CIMAHI - Cintantya Andhita Dara Kirana; Oktarizka Reviandani; Alfina Damayanti (Universitas Halu Oleo, 2022)
Poverty is one of the main causes of hunger. In 2020 based on the GHI or Global Hunger Index report, Indonesia scored 19.1. BPS noted that malnutrition rates in Indonesia reached 30,000 or one out of every 10,000 residents. One in three babies in Indonesia is diagnosed with stunting where the number of stunted toddlers in Indonesia is still at 30.7%. Some efforts that can be made to overcome hunger levels and reduce stunting rates include improving food intake, parenting, and paying attention to sanitation and providing clean water to the community. One of the programs that is being optimized by the government to improve the level of public health and nutrition by running an Additional Feeding Program (PMT). Cimahi city is a city with stunting rates in toddlers reaching 11.01% and stunting in toddlers reaching 9.87%. Government Regulation No. 42 of 2013 regulates the National Movement for The Acceleration of Nutrition Improvement, Improvement of Community Nutrition through The Additional Feeding Program (PMT) is one of the government programs implemented to reduce stunting rates and improve community nutrition in Cimahi City.